2015
DOI: 10.1542/peds.2014-2502
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perceptions of Light and Intermittent Smoking in the United States

Abstract: BACKGROUND: Light smoking, consuming a few cigarettes daily, and intermittent, or nondaily, smoking patterns are increasingly common but carry health risks comparable to heavier smoking patterns. Nearly all smokers begin smoking as adolescents, who are at risk for developing these smoking patterns. Previous research suggests that smokers underestimate the risks associated with smoking. The extent to which adolescents perceive light and intermittent smoking as harmful has not been previously assessed.METHODS: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 32 publications
(34 reference statements)
6
41
1
Order By: Relevance
“…Conversely, cigarette use was associated with beliefs that noncigarette products were more harmful, underscoring how adolescents perceive whichever product they use as less harmful. Corroborating existing research on adolescent tobacco perceptions, 19,21,34 findings reported here extend 7 .030…”
Section: Figuresupporting
confidence: 85%
See 2 more Smart Citations
“…Conversely, cigarette use was associated with beliefs that noncigarette products were more harmful, underscoring how adolescents perceive whichever product they use as less harmful. Corroborating existing research on adolescent tobacco perceptions, 19,21,34 findings reported here extend 7 .030…”
Section: Figuresupporting
confidence: 85%
“…Those who lived with a household member who used these tobacco products were more likely to contend that products were less harmful and addictive, findings previously observed. 19,21,34 Differences by ethnicity and gender also reflect this finding, with adjusted analyses finding that non-Hispanic white and male students, groups with the highest rates of e-cigarette use, 28 were more likely to view e-cigarettes, as well as smokeless tobacco products, as less harmful than cigarettes. Nonetheless, in all subgroups of e-cigarette-naive respondents and in most subgroups of e-cigarette users assessed, perception of relative safety has increased over the past few years, seemingly indicating a global change in youth attitudes toward these products.…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…Usually, intermittent and light smokers tend to underestimate the harm of cigarette consumption. They also display a tendency not to perceive themselves as "traditional" cigarette smokers, but rather as being more similar to nonsmokers (49,50). Despite these observations, intra-group differences do exist in risk perception between younger and older adolescents: older adolescents consider light smoking and intermittent cigarette smoking as more dangerous than younger adolescents (49).…”
Section: Light and Intermittent Cigarette Smokersmentioning
confidence: 99%
“…Adolescence is a critical period for the beginning of health-related risk behaviors such as smoking [1]. Between 12~22% of adolescents in the USA and 27~30% in Europe have smoked cigarettes at some point [2].…”
Section: Introductionmentioning
confidence: 99%